Study of body fluid samples using flow cytometry: Six years of experience at the Hospital Universitario San Ignacio - Campos, Alba (2017)
Flow cytometry (FCM) was implemented in 2008 at the Pontificia Universidad Javeriana and later at the Hospital Universitario San Ignacio to examine special samples of patients with hematological malignancies and solid tumors other than bone marrow and peripheral blood for diagnosis and monitoring. This study describes the main findings of special sample evaluation over a six-year period. In all, 1070 samples of body fluids from patients with benign and malignant diseases were examined by FCM. These samples were stabilized with TransFixTM and stained with six-color immunophenotyping panels. Samples included cerebrospinal fluid, bronchoalveolar lavage, pleural fluid, pericardial fluid and ascite fluid from patients with acute and chronic leukemia, myelodysplastic syndromes, lymphomas, myeloma, autoimmune diseases, immunodeficiencies and solid tumors, among others. Flow cytometry provided important information for the classification and detection of minimal numbers of tumor cells in leukemia and lymphoma cases. This work represents the first national report describing FCM implementation in special samples for diagnosis and clinical monitoring of patients with malignant and benign pathologies.